A summer monsoon pump to keep the Bay of Bengal salty. Issue 9 (14th May 2013) - Vinayachandran, P. N.; Shankar, D.; Vernekar, Siddharth; Sandeep, K. K.; Amol, P.; Neema, C. P.; Chatterjee, Abhisek
<x xml:space="preserve">Abstract</x> [1] The Bay of Bengal receives a large influx of freshwater from precipitation and river discharge. Outflow of excess freshwater and inflow of saltier water is required to prevent the bay from freshening. Relatively fresh water flows out of the bay along its boundaries and inflow of saltier water occurs via the Summer Monsoon Current (SMC), which flows eastward from the Arabian Sea into the bay. This saltier water, however, slides under the lighter surface water of the bay. Maintaining the salt balance of the bay therefore demands upward mixing of this saltier, subsurface water. Here, we show that an efficient mechanism for this mixing is provided by upward pumping of saltier water in several bursts during the summer monsoon along the meandering path of the SMC. Advection by currents can then take this saltier water into the rest of the basin, allowing the bay to stay salty despite a large net freshwater input.